(untitled) (Global Journal of Human-Social Science, 2021)
In the era of modernization and globalization climate changes and environmental degradation are the big threat for all the species of earth and their sustainability. The indigenous ecological knowledge and behaviour of the tribal people towards nature is generally based on sustainability, productivity and optimum balanced utilization of available land and other natural resource. In India the total tribal population is 8.6% of which 89.97% live in rural areas. This subcontinent is the largest tribal populated country where different ethnic groups co-exist in a same territory with their diversified traditional culture. A Major portion of tribal people inhabits in the northeast part of India and Khasi is one of them. They live in different states of India such as in Meghalaya, Assam, and Manipur but the major portion of the total Khasi population is found in north east forest region of Meghalaya. They are the ecological components of this forest ecology. Their intra and interconnection with nature is always symbiotic. But due to the globalization, the influence of modern culture, intermingling and cultural hegemony, most of the tribal cultures are in the way of extinction. Rural people tend to imitate the modern culture without thinking the effects and want to get shifted in urban areas for better facilities and livelihood opportunities.